THE IMAGE OF THE TOUGH WOMAN IN THE NOVEL ABOUT YOU BY TERE LIYE: ANALYSIS OF LIBERAL FEMINISM NAOMI WOLF - Ivi Wiske Panambunan; Syafri Badaruddin; Prasuri Kuswarini (International Journal of Social Science, 2022)
This study aims to describe the image of women through the main character in the novel About You by Tere Liye. The collection of data used in this study with a literature review. The data set is data on the image of women in the novel About You. The method used in this study is a qualitative descriptive method, because the data in this study are in the form of words. This study uses Naomi Wolf's liberal feminist analysis. Based on the results of research that has been carried out on the Novel About You by Tere Liye, the main character Sri Ningsih displays the image of a tough woman. Through the strength and power displayed by the main character in the novel. The main character shows the power that creates freedom through the strength and power of women, namely intelligence, charm, courage and courage. And, the function of women's power is leadership. All of these things are described by Sri Ningsih who is a tough woman in the novel About You.